2014
DOI: 10.7863/ultra.33.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Vasa Previa Across Gestation Using a Screening Protocol

Abstract: The use of standardized screening for vasa previa based on focused criteria was found to be effective in diagnosing vasa previa, with a 100% survival rate. Vasa previa diagnosed during the second trimester resolves in approximately 25% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(117 citation statements)
references
References 13 publications
6
110
0
1
Order By: Relevance
“…In one case report, the diagnosis of VP was made at the time of laser photocoagulation of communicating anastomoses in a MCDA twin pregnancy complicated by twin-twin transfusion syndrome 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 10 10 (TTTS). 27 The authors of two case reports 26,27 and of four cohorts [31][32][33][34] described the use of CL measurements in their management of twin pregnancies presenting with VP on antenatal ultrasound.…”
Section: Systematic Review Synthesis Of Resultsmentioning
confidence: 99%
“…In one case report, the diagnosis of VP was made at the time of laser photocoagulation of communicating anastomoses in a MCDA twin pregnancy complicated by twin-twin transfusion syndrome 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 10 10 (TTTS). 27 The authors of two case reports 26,27 and of four cohorts [31][32][33][34] described the use of CL measurements in their management of twin pregnancies presenting with VP on antenatal ultrasound.…”
Section: Systematic Review Synthesis Of Resultsmentioning
confidence: 99%
“…In placenta previa, it was demonstrated that the risk of peripartum bleeding becomes higher when the placental edge is located within 2cm of the internal os. 8 Extrapolating from this, Rebarber et al 1 proposed the same cut-off value of 2cm in the definition of low-lying VP, although there has been no convincing evidence that perinatal mortality becomes higher when the membranous fetal vessels are located within 2cm of the internal os.…”
Section: Discussionmentioning
confidence: 99%
“…1 The membranous fetal vessels can either lead from the placenta to a velamentous cord insertion (type 1) or connect the main bulk of the placenta to a succenturiate lobe (type 2). 2 The localization of the membranous fetal vessels can be classified as overlying (located directly over the internal os) or low-lying (located apart from the internal os but in front of the fetal presenting part).…”
Section: Introductionmentioning
confidence: 99%
“…32 Currently, asymptomatic patients with vasa previa are managed Ultrasound pictures of low-lying placenta and vasa previa A, Measurement of the distance between internal os and placental edge is L ¼ 1.41 cm (internal cervical os and placental edge are marked by þ signs); measurement of placental edge thickness (red double arrow) in low-lying placenta is performed within 1 cm (yellow line ¼ 1 cm); the angle (white dotted lines) between the basal and chorionic plate is >45 degrees. Vasa previaeaberrant fetal vessel is running B, exactly behind internal cervical os (arrow) or C, in close proximity (0.3 cm) to internal cervical os.…”
Section: Vasa Previamentioning
confidence: 97%
“…In all such cases a repeat ultrasound examination in the early third trimester is advisable to rule out vasa previa. 7,8 The diagnosis may be confirmed by transvaginal ultrasound using color Doppler demonstrating that at least 1 aberrant vessel is within 2 cm from the internal cervical os 32 (Figure 2, B and C). It should be noted that this definition within 2 cm from the internal cervical os was modeled after the existing definitions for low-lying placentas.…”
Section: Vasa Previamentioning
confidence: 98%